أعلام وحدود الحرم المكي الشريف - Al-Thubaiti | الثبيتي, Saud bin Musaad | سعود بن مسعد; Al-Thabiti | الثبيتي, Khadran bin Khadr | خضـران بـن خضـر (Makkah History Center | مركز تاريخ مكة المكرمة, 2023)
This book is a scientific document in knowing the locations and boundaries of the flags of the Holy Mosque in Makkah, their characteristics and their geographical names, equipped with photos, maps, tables and illustrative graphs, describing the state of these flags at the present time, proposing a number of useful steps in preserving them. The Center is pleased to place this book in the hands of the esteemed readers, hoping that it will be of benefit and benefit to every knowledgeable and researcher. | يعد هذا الكتاب وثيقة علمية في معرفة مواضع أعلام الحرم المكي الشريف وحدوده، وخصائصها وأسمائها الجغرافية، ً مزودا بالصور والخرائط والجداول والرسوم البيانية التوضيحية، واصفًا حال هذه الأعلام في الوقت الحاضر، مقترح ًا عددا من الخطوات المفيدة في المحافظة عليها. ، ويسعد المركز أن يضع هذا الكتاب بين أيدي القراء الكرام ً راجيا أن يتحقق به النفع وتحصل الفائدة لكل مطلع وباحث.